ANALISIS FAKTOR-FAKTOR PEMILIHAN TRANSPORTASI ONLINE: (Studi Kasus: Pemilihan Ojek Online Di Kota Tasikmalaya) - Raya Prima, Gary (Menara: Jurnal Teknik Sipil, 2023)
Online motorcycle taxis are a type of transportation that is widely used to support daily activities. The purpose of this study is to analyze what factors are considered in choosing an online motorcycle taxi. The method used is to form a linear regression equation model with four variables, including ease of use (X1), tariff (X2), security (X3), and efficiency (X4). The results obtained from the research equation model Y = 6.682 + 1.469 X1 + 0.456 X2 + 0.773 X3 + 0.945 X4. The results of the test for the coefficient of determination (R) are 52.6%, the choice of online motorcycle taxis is influenced by these variables. The F test shows F count (26.396) > F table (2.699), meaning that the independent variable X has a significant effect simultaneously on variable Y. The t test shows t count values X1 (3.432), X2 (2.425), and X4 (3.201) > from t table (1.98498), meaning that these variables have a partial effect on Y. Meanwhile, t count X3 (1.520) < t table (1.98498), then variable X3 has no partial effect on Y.